Phylogenic analysis of Escherichia coli strains isolated from young alpacas (Vicugna pacos) with diarrhoea in the central Peruvian Andes - Sicha R., Francisco (2020)
The aim of this study was to determine the phylogenetic groups of Escherichia coli isolated from alpacas with diarrhoea. The presence of E. coli was determined in 150 samples of diarrheal faeces collected from young alpacas from the central highlands of Peru, and the distribution of phylogenetic groups was determined by the Clermont method. E. coli was present in 79.3% (119/150) of animals with diarrhoea. The strains were classified into phylogenetic groups A, B1, B2 and D, which showed a frequency of 13.5% (16/119), 65.5% (78/119), 1.68% (2/119) and 19.33% (11/23), respectively. Moreover, 21% (25/119) of isolated strains of E. coli belonged to phylogenetic groups B2 and D, mainly extraintestinal pathogenic strains, and 79% (94/119) to groups B1 and A, which are mainly commensal strains.